The Effects of Bullying: A Comparison of Northern Sotho Folktales and Real Life Situations - Seleka Maria Tembane (E-Journal of Humanities, Arts and Social Sciences)
Bullying occurs when an individual is subjected, repeatedly over time, to negative actions perpetrated by others who possess greater physical, social, and intellectual power. Bullying is an extremely challenging situation for anyone. It induces feelings of dread and degradation and frequently makes one feel worthless. Since time immemorial, bullying has been a common practice in all societies and this is reflected in folktales. This article addresses the danger of bullying and its impact on real-life situations as compared with situations in folktales. The present article analysed the manner in which folktales might offer lessons on the consequences of bullying, such as moral and social punishment, and how these lessons might influence societal attitudes toward bullying in the Northern Sotho-speaking community. The Functional Attitude Theory was employed as a framework because bullies in the folktale and in real-life situations adopt attitudes that are essential to their psychological benefit. Data was analysed using a descriptive qualitative approach. Secondary data such as published books, dissertations, articles, and theses were used as methods of data collection. The study revealed that there are different lessons employed in folktales to prevent bullying in societies. It is therefore recommended that additional works of literature in African languages be produced to educate societies about the possible negative effects of bullying. This study might shed light on how cultural narrative-shaped attitudes can be used to lessen bullying. Employing storytelling as a teaching method in schools may aid in dispelling unfavourable preconceptions or antagonistic attitudes that contribute to bullying.